ANALYTICAL PLATFORM FINANCIAL AND ECONOMIC TRENDS IN CONTEMPORARY GEOPOLITICAL AND SCIENTIFIC AND TECHNOLOGICAL TRANSFORMATION: THE WORLD AND RUSSIA - Petr Akinin; Sabiyat Magomedsaidova; Valentina Akinina (Вестник Северо-Кавказского федерального университета)
We consider global trends and domestic financial - economic development under the influence of revolutionary processes in geopolitics, science and technology. Central to the ongoing transformations are highlighted: the crisis of the liberal model and the development of alternative approaches; the formation of the digital economy and the emergence cryptocurrency; development of new industrialization, based on the formation of the sixth technological order; changes in production and energy consumption. The role of Russia in opposition to the unipolar world. Reasoned postulate that the most dynamic vector of new industrialization are the information and communication technology (IT), the emerging digital economy.